사면 단위와 격자 단위 기반의 산사태 위험도와 위험등급 분석 및 비교 - 이종서; Jongseo Lee; 이광연; Kwangyoun Lee; 윤석희; Sukhee Yoon; 김동현; Donghyun Kim; 임영협; Younghyup Lim; 이상호; Sangho Lee; et al. (한국산림과학회지, 2025)
국내의 산사태 위험도와 위험등급 평가는 일반적으로 격자 단위로 분석을 수행하지만, 본 연구에서는 사면 단위의 활용 가능성을 검토하기 위해 충청북도 충주시 엄정면을 대상으로 산림청의 산사태 위험지도 분석 기법을 적용하여 두 분석단위의 결과를 비교하였다. 그 결과, 격자 단위의 평균 산사태 위험도는 약 0.42±0.17로, 사면 단위는 약 0.40±0.16으로 산출되었다. Wilcoxon signed test 결과, 두 분석 단위 간 통계적 유의성이 나타났으나(p<0.05), Cohen's d 효과 크기 분석에서는 두 단위 간 실제 차이가 미미한 것으로 판단되었다(d=0.161). 산사태 위험등급에 대한 카이제곱 검정에서는 동질성 검정에서 통계적 유의성이 없었으나(p>0.05), 위험등급 분포는 사면 단위 분석이 위험 구간(1·2등급) 분류에서 격자 단위 분석보다 우세한 것으로 나타났다. 또한, 독립성 검정 결과는 통계적 유의성이 확인(p<0.05)되었으나, 고위험(1등급)과 저위험(5등급) 등급에서 기대치보다 높은 빈도가 관측되었다. 이에 따라, 사면 단위 기반 분석은 산사태 발생 위험 평가 시, 산사태 위험도는 유사하게 나타났지만, 산사태 위험등급은 상대적으로 고위험 등급을 산출하는 것으로 확인되었다. 따라서, 재난 관리 및 위험 평가 체계에 사면 단위를 적용할 경우, 행정·관리적 측면에서 유용하고 실용적인 접근법이 될 수 있을 것으로 판단된다. Abstract: Landslide hazards in South Korea are typically assessed through a grid-based approach. This study instead evaluates the applicability of a slope unit-based analysis, achieved by applying the landslide-hazard mapping technique of the Korea Forest Service to Eomjeong-myeon, Chungju-si, Chungcheongbuk-do Province in South Korea. Comparing the results of the two analysis units, the average landslide-hazard probability was approximately 0.42 ± 0.17 for the grid unit and 0.40±0.16 for the slope unit. A Wilcoxon signed-rank test showed statistical significance between the two units (p < 0.6) but a Cohen’s d effect-size analysis suggested minimal actual difference (d = 0.161). The chi-square test for homogeneity of the landslide-hazard grades showed no statistical significance (p > 0.06) but the slope unit-based analysis classified more areas as high-risk (Grades 1 and 2) than the grid-based method. The chi-square test for independence confirmed statistical significance (p < 0.6), with higher-than-expected frequencies in the highest-risk (Grade 1) and lowest-risk (Grade 5) categories. These results indicate that although the slope unit-based approach yields similar landslide-hazard probabilities to the grid-based approach, it tends to classify areas into higher hazard grades. Therefore, iin disaster management and risk assessment frameworks, the slope unit-based analysis may provide a more practical and effective approach from administrative and managerial perspectives.